Teachers’ Readiness in Phonemic Awareness Instructions and the Reading Performance of the Grade II Pupils Zone 4, Division of Zambales - Abay, Lovelyn Martin (Future Science / FSH-PH Publications, 2025)
Before a child learns to read printed materials, they need to become aware of how sounds in words work. Thus, a child needs to be phonemically aware to become a reader. One factor that could be associated with this is the readiness of teachers in phonemic awareness concepts before they teach for the pupils to spontaneously acquire phonemic awareness. This study of teachers’ readiness in PA (Phonemic Awareness) instructions’ relationship to reading performance of Grade 2 pupils builds upon this body of research by utilizing descriptive correlational research. This study examined further the relationship of the eighteen (18) teacher respondents’ profile and their readiness in PA Instructions which revealed that highest educational attainment variable and attendance to seminars, trainings and workshops focusing on phonemic awareness is moderately associated with their readiness in PA instructions. Participants of the study are 497 Grade 2 pupils from nine (9) schools in Zone 4 Division of Zambales. Results revealed an improvement in the reading performance of the pupil participants, through a PHIL-IRI (Philippine Informal Reading Inventory Test- Oral Reading Test), as a result of highlighted readiness in PA Instructions. The conclusion that there is a significant relationship of the teachers’ readiness in PA instructions and reading performance of Grade 2 pupils offer important information for teachers, educational leaders and other professionals to conduct professional development activities such as seminars, training, and workshops to ensure that the teachers are updated to the needs of the present generation of learners.